8. Nacionalna konferenca o varnosti v lokalnih skupnostih: Cilji trajnostnega razvoja in varnost v lokalnih skupnostih - Marina Bajić; Meško, Gorazd; Kokoravec, Iza (2022)
8th National Conference on Local Safety and Security: Sustainable Development Goals and Safety and Security in Local Communities. The conference proceedings contain peer-reviewed papers that were presented at the 8th National Conference on Safety and Security in Local Communities in Celje in December 2022. The main theme of the conference remains safety and security in local communities, however, this time the focus was the presentation and analysis of the Sustainable Development Goals of the United Nations. Papers are the result of research within the research programme Safety and security in local communities – comparison of rural and urban environments, conducted at the Faculty of Criminal Justice and Security, University of Maribor and cooperation with practitioners in the field of security. Papers in the proceedings focus on various aspects of ensuring safety and security in local communities in connection with the goals of sustainable development, the connection between the goals of the research programme and the goals of the 2030 Agenda for sustainable development, and they also address challenges and suggestions for future work.
Keywords: local communities; safety and security; sustainable development goals; research programme; Slovenia